Dental health state of children living in different anthropogenic condition - Luchynskyі, M. A. (Journal of Education, Health and Sport, 2015)
Luchynskyі M. A. Dental health state of children living in different anthropogenic conditions. Journal of Education, Health and Sport. 2015;5(11):170-178. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.33698 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A170-178 https://pbn.nauka.gov.pl/works/668515 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 10.11.2015. DENTAL HEALTH STATE OF CHILDREN LIVING IN DIFFERENT ANTHROPOGENIC CONDITIONS Luchynskyі M. A. I. Y. Horbachevskyy Ternopil State Medical University of Ministry of Health of Ukraine, Ukraine, Ternopil (Ternopil, Maydan Voli, 1, 46001) Abstract The purpose of the work is to study dental health of children living in conditions of combined negative impact of natural and technological factors. Materials and methods. It was performed an epidemiological dental examination of 2,551 children aged 6 to 15 years, who settled in different regions of the Precarpathians, in conditions of iodine and fluoride deficiency (plain - 1087 children, foothills - 730 and mountain - 734 children). Results. Comprehensive epidemiological studies found low levels of dental health of children living in different geochemical and anthropogenic conditions of Ivano-Frankivsk region (48,83 ± 0,36)% in the general observation, that is not statistically different by regions examination, moreover girls level is lower, than that of boys in examined regions (48,14 ± 0,50) and (49,51 ± 0,52)%, respectively. It was founded, that the main diseases, which contribute to the reduction of dental health in children, is dental caries and its complications and abnormalities of dentoalveolar system. It was found, that the frequency and severity of dentoalveolar abnormalities depend on anthropogenic environmental conditions: in children of plain and foothill regions, that suffer from greater anthropogenic pressure, dentoalveolar abnormalities where found in (67,99 ± 1,42) and (65,21 ± 1,76)%, against (45,91 ± 1,84)% in children of conditionally pure mountain region. These same children also often recorded more severe pathology – combined anomalies (24,09 ± 1,57) and (22,06 ± 1,90)%, against (12,17 ± 1,78)%, respectively). It was found the connection between the dentoalveolar abnormalities and the presence of caries (r = + 0,95; p <0,01) and periodontal tissue diseases (r = + 0,79; p <0,05). Keywords: children, dental health, dentoalveolar abnormalities, dental caries, periodontal disease, hypoplasia.